A comparison of measurement methods of hippocampal atrophy rate for predicting Alzheimer's dementia in the Aberdeen Birth Cohort of 1936. Issue 1 (23rd December 2016) - Rana, Arnab K.; Sandu, Anca‐Larisa; Robertson, Kenna L.; McNeil, Christopher J.; Whalley, Lawrence J.; Staff, Roger T.; Murray, Alison D.
Abstract: Introduction: Various methods are available to measure hippocampal atrophy rate. We compared methods to predict Alzheimer's dementia. Methods: Participants with brain imaging at ages 69 and 73 years were identified from a previous study. Simple manual measures and computationally automated volumetry were performed. Receiver operating characteristics assessed the predictive ability of each method at baseline and on logit regression analysis of two serial scans. Results: Ten of 149 participants developed Alzheimer's dementia and had lower baseline volumes (3647 vs. 4194 mm 3 P  = .002), rates of volume loss (−126 vs. −36 mm 3 /y; P  = .001), and rates of loss in hippocampal fraction (−8.55 vs. −2.35 x 10 −5 /y; P  = .001). Baseline volume with a rate of change gave the highest area under the curve value of 0.96. Discussion: Automated volumetry measuring hippocampal size at age 69 years and subsequent rate of change predicts Alzheimer's dementia development.